Minimally invasive esophagectomy in the lateral‐prone position: Experience of 124 cases in a single center. Issue 1 (23rd October 2017) - Ma, Shaohua; Yan, Tianshen; Liu, Dandan; Wang, Keyi; Wang, Jingdi; Song, Jintao; Wang, Tong; He, Wei; Bai, Jie; Jin, Liang
Abstract : Background: Minimally invasive esophagectomy was first introduced as a new technique for esophageal cancer treatment 20 years ago. Performing this procedure in the lateral‐prone position is the most appropriate method. Since May 2013, our center has performed 124 esophageal cancer operations using this procedure. Herein, we share our experience. Methods: We retrospectively reviewed 124 consecutive patients who had received minimally invasive esophagectomy in the lateral‐prone position from May 2013 to June 2017. The procedure, operative variables, postoperative complications, and oncology outcomes were assessed. Results: The surgery was successful in all 124 patients; three cases converted to an abdominal opening procedure during surgery. The mean total lymph node harvest was 19.2: 12.9 in the thoracic cavity and 6.0 in the abdominal cavity. The average total operation duration was 376 minutes and blood loss was 156 mL. No mortality occurred within 30 postoperative days. Forty‐three cases of postoperative morbidity occurred in 38 patients (30.6%), including 11 anastomotic leakages (8.9%), 1 chyle leak (0.8%), 12 lateral recurrent nerve palsies (9.7%), 11 pulmonary complications (8.9%), and 8 other complications (6.5%). A learning curve indicated that blood loss, operation duration, and the number of lymph nodes harvested would improve with time. Conclusions: Surgical and oncological outcomes following minimally invasive esophagectomy for esophageal cancer were acceptable. There are some advantages to this technique compared to previous reports of opening procedures.